Edukasi Public Speaking Anak Panti Asuhan Graha Yatim Dhuafa Surabaya - Yoga Mega; Aza Ruvidyansah; Raka Putra S; Veronika Imanuel Puraji; Monica Lewinsky; Moch. Arkansyah (Prapanca : Jurnal Abdimas, 2022)
In this digital era, the need for information and technology is slowly growing. However, people are lulled by the ease and sophistication of technology, therefore we need to limit it, especially children who are still underage. Understanding of digital media and learning public speaking needs to be given and introduced to minors with the aim of preparing for character education and children's social skills in the future. The targets of this research are children who are in the Graha Yatim Dhuafa Orphanage, Surabaya City. The research method used is a qualitative method with a descriptive approach, the results obtained from this study are the children's ability to communicate and socialize and are ready for the development of technology and information.